Chances and drawbacks of derepressed recombinant enzyme production in continuous cultivations with Komagataella phaffii - Besleaga, Mihail; Ebner, Katharina; Glieder, Anton; Spadiut, Oliver; Kopp, Julian (Frontiers in Bioengineering and Biotechnology, 2025)
Utilizing Komagataella phaffii (K. phaffii) as a host, methanol-dependent fed-batch cultivations remain state-of-the-art for recombinant protein production. Recently, however, derepressible promoters have emerged as a valuable methanol-free alternative, especially for the expression of complex target proteins. In this study, we investigated the expression of a recombinant model enzyme (UPO) using a derepressible bi-directionalized promoter system in continuous cultivations. According to the literature, low growth rates required for derepression might result in pseudohyphae growth in chemostat cultivations with K. phaffii. This phenotype would be highly undesired as pseudohyphae growth is referred to decreasing productivity. Still, literature on derepressible promoter systems used in continuous cultivations is scarce. Hence, we aim to investigate pseudohyphae growth in a derepressible bi-directionalized promoter system. Several chemostats and a decelerostat screening were performed to identify the effect of the specific growth rate on pseudohyphae growth in continuous cultivations whilst monitoring the productivity of the recombinant target enzyme. Based on the experimental screening data, derepression was still achieved at a growth rate of 0.11 h-1, whilst no pseudohyphae growth was observed. However, verifying these conditions for an extended timeframe of more than five residence times triggered pseudohyphae formation. Hence, the results of this study indicate that pseudohyphae growth in chemostats with derepressible promoter systems in K. phaffii is both growth-rate and time-dependent, thus limiting the potential of continuous cultivations for recombinant production of UPO. Despite the observed limitations, we still propose decelerostat cultivations as a proper screening tool to determine suitable production conditions in continuous systems for derepressed promotors.